Strengthening Deep Learning for Rural Elementary School Teachers through Local Wisdom-Based Pentigraphs as Innovative Interactive Literacy Media - Mardiningsih Mardiningsih; Dies Nurhayati; Ayu Maya Damayanti (Universitas Nurul Jadid, 2025)
This community engagement program empowered rural public elementary school teachers in Grati Subdistrict, Pasuruan Regency, East Java, to develop local wisdom-based literacy media using the folktale The Origin of Lake Ranu Grati. This location was selected because the partner schools are close to Lake Ranu Grati and the folktale remains a living oral tradition, yet it has not been used systematically as classroom material. The program responded to needs identified in an initial assessment: limited integration of local cultural content in learning (86%) and limited creative writing and digital media competence (78%). Using a participatory empowerment method, the program was implemented through five connected stages: outreach to identify needs and agree on outputs, training with mentoring to build skills, monitoring to ensure implementation progress, evaluation to measure impact, and continuation to support sustainability through a teacher forum and school literacy agendas. Teachers wrote three-paragraph short stories (pentigraf) based on the folktale and then transformed the texts into multimodal literacy media, including comics, an interactive e-book, and short animations for classroom use. Evaluation using rubrics and questionnaires showed an average 90% improvement in pentigraf writing skills and an 85% increase in teachers’ use of local potential as teaching media, alongside observable practice changes such as consistent drafting and revision through feedback cycles and greater initiative to create and use culture-based media in lessons. The main outputs were published as an ISBN and E-ISBN anthology and e-book titled Kisah Yang Tumbuh Dari Danau.